2016
DOI: 10.1002/cncr.30247
|View full text |Cite|
|
Sign up to set email alerts
|

Next‐generation sequencing survey of biliary tract cancer reveals the association between tumor somatic variants and chemotherapy resistance

Abstract: Background BTC are uncommon and associated with a dismal prognosis. Gemcitabine and platinum-combinations (GP) form the standard approach for treating advanced BTC. To characterize the spectrum of mutations and to identify potential biomarkers for GP response in BTC, we evaluated the genomic landscape and assessed whether mutations affecting DNA repair were associated with GP resistance. Methods Pretreatment FFPE samples from 183 BTC patients treated with GP were analyzed. Cox regression models were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…In triple-negative breast cancer, WEE1 inhibition overcame cisplatin resistance by disrupting DNA replication and G2/ M cell cycle checkpoint regulation [20]. A clinical trial also revealed that BTC patients harboring DDR-related gene mutations responded better to cisplatin therapy than those with wild-type cancer [21]. Because cytotoxic chemotherapy is the standard treatment for advanced BTC, targeting DDR signaling pathways is extremely important for improving the efficacy of chemotherapeutic agents against BTC.…”
Section: Discussionmentioning
confidence: 99%
“…In triple-negative breast cancer, WEE1 inhibition overcame cisplatin resistance by disrupting DNA replication and G2/ M cell cycle checkpoint regulation [20]. A clinical trial also revealed that BTC patients harboring DDR-related gene mutations responded better to cisplatin therapy than those with wild-type cancer [21]. Because cytotoxic chemotherapy is the standard treatment for advanced BTC, targeting DDR signaling pathways is extremely important for improving the efficacy of chemotherapeutic agents against BTC.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of next‐generation sequencing has revealed somatic genetic alterations in biliary cancer that are important prognostic factors and potentially predictive of treatment response and survival . Nearly all patients with biliary tract cancer will have at least 1 oncogenic somatic molecular alteration identified by next‐generation sequencing analysis . The most commonly mutated genes are CDKN2A , TP53 , and KRAS with an estimated incidence of more than 20% of patients with biliary tract tumors.…”
Section: Introductionmentioning
confidence: 99%
“…17 Activating KRAS mutations are present in 16-22% of BTCs. [18][19][20] mTOR inhibitors are approved for the treatment of renal cell, neuroendocrine and hormone-positive/HER-2-negative advanced breast cancer. [21][22][23] Recently, the phase II Italian Trials in Medical Oncology (ITMO) trial assessed everolimus activity in patients with chemorefractory advanced BTC, where a favourable toxicity profile and encouraging anti-tumour activity was reported.…”
Section: Introductionmentioning
confidence: 99%